1992
DOI: 10.1073/pnas.89.15.6896
|View full text |Cite
|
Sign up to set email alerts
|

Large induction of keratinocyte growth factor expression in the dermis during wound healing.

Abstract: Recent studies have shown that appliaton of basic fibroblast growth factor (basic FGF) to a wound has a beneficial effect. However, it has not been whether endogenous FGF also plays a role in tissue repair. In this study we found a 160-fold induction of mRNA encoding keratinocyte growth factor (KGF) 1 day after skin injury. This large induction was unique within the family of FGFs, since mRNA lvel of acidic FGF, basc FGF, and FGF-5 were only slightly induced (2-to 10-fold) during wound healing, and there was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
363
4
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 551 publications
(394 citation statements)
references
References 30 publications
23
363
4
4
Order By: Relevance
“…A band of the expected size was detected 1 day after injury, and the level of induction continued to increase to a maximum at 5 days (Figure 7). This pattern was consistent with the temporal pro®le of KGF induction at wound sites documented previously using this animal model (Werner et al, 1992), suggesting that the NDF induction we observed was the result of locally increased KGF activity.…”
Section: Induction Of Ndf In Response To Injury In Vivosupporting
confidence: 92%
See 2 more Smart Citations
“…A band of the expected size was detected 1 day after injury, and the level of induction continued to increase to a maximum at 5 days (Figure 7). This pattern was consistent with the temporal pro®le of KGF induction at wound sites documented previously using this animal model (Werner et al, 1992), suggesting that the NDF induction we observed was the result of locally increased KGF activity.…”
Section: Induction Of Ndf In Response To Injury In Vivosupporting
confidence: 92%
“…The induction of NDF was detected in a mouse model of skin wound healing where KGF has been shown to be strongly upregulated within 24 h after injury (Werner et al, 1992). We also observed signi®cant NDF induction in the kidneys of partially hepatectomized mice, where circulating HGF levels are increased in response to liver failure (Kinoshita et al, 1991;Lindroos et al, 1991).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…These growth cytokines are known to stimulate cell proliferation, migration, differentiation, cell survival, and protein synthesis, and have been shown to enhance healing of wounds 42, 43, 44, 45. Additionally, TIMP‐1, which was also upregulated, is an inhibitor of MMPs and is actively involved in tissue remodeling processes 46…”
Section: Discussionmentioning
confidence: 99%
“…11 Several types of FGFs are expressed at the wound site, including FGF1, FGF2, FGF7, FGF10, and FGF22, and the expression of some of them is greatly increased at different phases of the repair process. 12,13 This is functionally important because FGF2 knockout mice have impaired wound healing, 14 and expression of a dominant-negative FGFR2 mutant in keratinocytes of transgenic mice resulted in a severe delay in wound re-epithelialization. 15 Therefore, FGF signaling is obviously required for efficient healing.…”
Section: Fgfs and Wound Repairmentioning
confidence: 99%